2007
DOI: 10.1111/j.1469-7998.2006.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Den shifting by wolves in semi‐wild landscapes in the Deccan Plateau, Maharashtra, India

Abstract: Reproductive success is crucial for the survival and persistence of any species. The Deccan Biogeographic Zone of India is the stronghold of a population of the Indian wolf Canis lupus pallipes. Gaining a better understanding of the den-use pattern of wolves in different areas in this zone is thus vital for their conservation and management. The wolves excavated multiple dens in our study sites and kept shifting their litters among them. Major disturbance factors around denning sites were active stone quarries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…We did not detect a significant effect of pup age on the tendency of packs to relocate pups following low-level disturbance, but given the data (i.e., 4 of 5 vs. 1 of 4 litters moved for pups >4 and 4 weeks of age, respectively) this likely reflects small sample sizes rather than a true lack of effect. Qualitatively, these results support the findings of Frame et al (2007) and Habib and Kumar (2007), who found age of pups at the time of disturbance to be important in influencing abandonment of disturbed homesites. Adult pack members may resist moving young pups because it is more risky owing to their small size, low mobility, and lack of independence (Packard 2003;Frame et al 2007).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We did not detect a significant effect of pup age on the tendency of packs to relocate pups following low-level disturbance, but given the data (i.e., 4 of 5 vs. 1 of 4 litters moved for pups >4 and 4 weeks of age, respectively) this likely reflects small sample sizes rather than a true lack of effect. Qualitatively, these results support the findings of Frame et al (2007) and Habib and Kumar (2007), who found age of pups at the time of disturbance to be important in influencing abandonment of disturbed homesites. Adult pack members may resist moving young pups because it is more risky owing to their small size, low mobility, and lack of independence (Packard 2003;Frame et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Pup age can also affect the response of a pack to human disturbance at the homesite (Chapman 1977;Frame et al 2007;Habib and Kumar 2007). We therefore tested for differences in response according to pup age, categorized as 4 and >4 weeks (below and above weaning age, respectively; Frame et al 2007) for homesites exposed to both levels of human disturbance using Fisher's exact test (Zar 1999).…”
Section: Immediate Responsementioning
confidence: 99%
See 2 more Smart Citations
“…In India, most of the studies have centred on the abovementioned primary questions (53.7%, 47.6% and 28.1% of studies, respectively). Only a few recent studies have looked further at hibernation [36], den shifting [37], social organization [38] and monitoring translocated and rehabilitated individuals [39]; however, the number of such studies remains low (Table 4). A poorly planned study often brings to the unnecessary use of telemetry where obvious results are presented as a final outcome.…”
Section: No Information 63mentioning
confidence: 99%